(untitled) (International Journal of Physiology, 2025)
This study was conducted in a hospital in the city of Tikrit from the first of December 2023 to the first of March 2024. The aim is to study the difference between the high and low concentrations of milk hormone in single and married women and to identify the dangers and benefits of high and low levels of this hormone, as samples were taken from both cases and at different ages and treated with (prolactin kit) from Accu Bind, and the level of milk hormone was measured. The results of the samples of married women suffering from high levels of milk hormone were the first group, and the mean of their ages was 33 years, and the arithmetic mean of the percentage of milk hormone in the blood of the samples was 24. As for the results of the samples of single women suffering from low levels of milk hormone, the mean age of the subjects was 30 years, and the arithmetic mean of the milk hormone ratio in the blood of the samples was 25.47, and the increase in milk hormone levels leads to many of the symptoms that appeared in the studied samples, including Delayed menstruation, the appearance of milk discharge in non-breastfeeding or single women, as well as a marked increase in the appearance of hair in the body areas in general. It was observed significances differences in patients from single women suffering from low milk hormone in the presence of an increase in the hormone dopamine, which is the hormone responsible for reducing the level of milk hormone, which is the result of a disorder in the pituitary gland due to some incorrectly prescribed medications, especially in cases of severe headaches.